The lecturing in english (LiE) programme: Lecturers' perception / Khairunisa Nikman, Zurah Abu and Hazlin Hasan - Nikman, Khairunisa; Abu, Zurah; Hasan, Hazlin (2012)
The English language plays a paramount role in our education system especially in the higher echelon of education. Almost all higher learning institutions in Malaysia such as UiTM, IIUM, USM, and other colleges use English as the medium of instruction in the. teaching and learning processes, In spite of that policy, there are still a large number of lecturers who are not competent and confident enough to use the language when delivering lectures. Therefore, the lecturers of The Academy of Language Studies, UiTM Pahang have taken the initiative to set up the Lecturing in English (LiE) Programme to help lecturers deliver lectures in English in a more effective manner. Thus, this study sets out to investigate the lecturers' perceptions of the LIE (Lecturing in English) programme. The respondents of this study comprised of 79 lecturers who were also the participants of the LiE (Lecturing in English) programme; they were from UiTM Pahang and other tertiary institutions all over Malaysia. In determining their perceptions towards the training programme, the data collection for this study was accomplished through an analysis of questionnaires. The findings from this study indicate that the participants of the programme rated the programme as good and they learned some new knowledge and skills from it The insights also conclude that the respondents felt that the LiE training programme had increased their confidence level and communication skills in delivering lectures in English.